Comparison between Rowatinex and Tamsulosin as a Medical Expulsion Therapy for Ureteral Stone - Ghassan S.Ahmed; Kassim J. Al-Shamma; Majeed M.Asghar (College of Pharmacy University of Baghdad, 2017)
The objective of this study is to evaluate the efficacy and safety of rowatinex and tamsulosin in the treatment of patients with ureteric stone. Forty patients with ureteric stone ranged (4- 12) mm, were included in this study. They were randomized into two groups where the first group includes twenty patients treated with Rowatinex three times daily (Group 1), and the second group includes twenty patients treated with tamsulosin 0.4mg/day (Group 2). All patients were randomly assigned to receive the designed standard medical therapy for a maximum of 3 weeks. Each group was given an antibiotic as prophylaxis and an injectable non-steroidal anti-inflammatory drug used on demand. At the outpatient clinic all subjects were assessed by CT-scan at baseline and evaluated every 7 days by physical examination, plain abdominal X-ray (KUB), and abdominal ultrasonography. Data were analyzed by using Student t-test method to compare the results; differences in the success rate between treatments were compared with the chi-square test for 2Ã- 2 tables. The results showed that tamsulosin significantly increases the expulsion rate, and reduce expulsion time of ureteric stone when compared with rowatinex group. Tamsulosin results in a better control of renal colic pain, and decreases in endoscopic procedures performed to remove the stone.  Key words: Ureteric stone, Tamsulosin, Rowatinex, Medical expulsion therapy.